ANALISA DAN PERANCANGAN SISTEM APLIKASI PEMBAYARAN ADMINISTRASI MENGGUNAKAN RFID BERBASIS CLIENT SERVER - Gunawan Wibisono; Vivi Kumalasari Subroto; Danang Danang (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
financial information in schools. Payment information which is the basis for schools to determine future policies. The object of research in this thesis is the Demak Development High School which is one of the agencies engaged in the field of science and education. The research objective is to design an effective and efficient school payment administration recording information system and design a school payment administration recording information system that has a system security that can maintain the accuracy of the data. The research method used is the Borg and Gall R&D Development Research model, the Prototyping System Development Method to produce a product in the form of a Prototype with 6 stages: Research and Data Collection, Planning, Initial Product Development, Product Testing, Product Revision, Final Trial. The conclusion from the results of this study is that this system can facilitate the recording of administrative payment transactions so that there are no mistakes in recording, users can easily present payment reports more quickly so that they can minimize recording time and recording errors, and make it easier for users to print payment reports with affectic and efficient results so as to support and accelerate decision making